BOShLANGʻICh SINF OʻQUVChILARINI TARBIYALAShDA MILLIY URF-ODAT VA AN’ANALARNING OʻRNI - Ismaylov, A.S.; Zeripbaeva, K. (SCIENCE and SOCIETY, 2025)
This article comprehensively explores the significant role of the national customs and traditions of the Uzbek people in educating primary school students as individuals with comprehensive intellectual potential.